1975
DOI: 10.1159/000180452
|View full text |Cite
|
Sign up to set email alerts
|

Function of the Kidney in Adult Patients with Cooley’s Disease

Abstract: The function of the kidney in adult subjects with Cooley’s disease has been hitherto inadequately investigated. In 10 patients suffering from thalassemia major, glomerular filtration rate, renal plasma flow, renal blood flow have been studied, together with urine concentration capacity. The authors emphasize certain pathological changes, such as the increase in renal plasma flow and the failure of the urine concentration ability. On the basis of renal biopsies, two pathogenetic theories are discussed: the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 5 publications
1
31
2
Order By: Relevance
“…In the study of Lapatsanis et al, increased hemoglobin level of patient group over 7.5 mg/dl was accompanied by increasing level of serum ALP; that increase was linked to improved osteoblastic dysfunction. Although mean hemoglobin level was 8.78 ± 0.71 mg/dl in our patient group, such an increase was not detected [9]. Phosphorus levels of thalassemia group were significantly higher in the control group (p <0.05).…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…In the study of Lapatsanis et al, increased hemoglobin level of patient group over 7.5 mg/dl was accompanied by increasing level of serum ALP; that increase was linked to improved osteoblastic dysfunction. Although mean hemoglobin level was 8.78 ± 0.71 mg/dl in our patient group, such an increase was not detected [9]. Phosphorus levels of thalassemia group were significantly higher in the control group (p <0.05).…”
Section: Discussioncontrasting
confidence: 66%
“…Many reasons are proposed, although mechanism of kidney dysfunction in thalassemia is not exactly known [9,10]. Increased [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity correlated with the degree of anemia is least severe in patients on hyper transfusion and iron chelation therapy, suggesting that the damage might be caused by the anemia and increased oxidation induced by excess iron deposits. [1][2][3][4][5][6][7][8][9] Although it was reported that urinary excretion of proximal renal tubular damage parameters increased in patients with TM and TI, renal functional parameters were not separately studied as glomerular and tubular markers in all types of the disease. The aims of the present study were to assess the glomerular and tubular renal functions in three different types of beta thalassemia, and to identify the similarities and differences between groups and to compare with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Renal involvement has been extensively studied in both Cooley’s disease and sickle cell anemia [1, 2, 3, 4, 5, 6, 7, 8] but sparingly in β-thalassemia/Hb E disease [9, 10]. There are several factors that may adversely affect the kidney in thalassemia: chronic anemia, iron overload, hemosiderosis and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%